1999
DOI: 10.1002/(sici)1099-1026(199903/04)14:2<112::aid-ffj786>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Constituents of the essential oil ofTanacetum (syn.Chrysanthemum) fruticulosum Ledeb. from Iran

Abstract: The essential oil of Tanacetum (syn. Chrysanthemum) fruticulosum Ledeb. from Iran was investigated by GC, GC–MS and NMR spectroscopy. The oil is characterized by photo‐oxidation products of lavandulol and nerolidol. Ninety‐seven components, representing 93% of the oil, could be identified. The oil contains mainly monoterpenes [1,8‐cineole (8), camphor (12), lavandulol (13), lavandulyl acetate (25)]. The new 5‐isopropenyl‐2,2‐dimethyltetrahydrofuran‐3‐yl‐methyl acetates (30, 31) are trace constituents. Some new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…The terpene alcohol lavandulol, and an incompletely characterized ester of lavandulol with 2-methylbutanoic acid have been described by other workers (28), but the specific ester with (R)-lavandulol and (S)-2-methylbutanoic acid has not previously been described. Maconelliol is an unusual cyclobutanoid monoterpene, and its structure has been established by enantioselective synthesis from precursors of known structure and configuration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The terpene alcohol lavandulol, and an incompletely characterized ester of lavandulol with 2-methylbutanoic acid have been described by other workers (28), but the specific ester with (R)-lavandulol and (S)-2-methylbutanoic acid has not previously been described. Maconelliol is an unusual cyclobutanoid monoterpene, and its structure has been established by enantioselective synthesis from precursors of known structure and configuration.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of the sex pheromone will also enable future development of mating disruption and attract-andkill technologies for managing M. hirsutus populations. The trial was conducted from July 8 to July 28,2003. Total number of male M. hirsutus captured was 18,291.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, many studies have reported on the essential oil compositions of various Tanacetum species. In the previous studies [2][3][4][5][6][7][8][9][10][11][12], camphor, 1.8-cineole, α-thujone, carvone, thymol, trans-sabinyl acetate, borneol, caryophyllone oxide, (E)-myroxide, sabinene, bornylacetate, and isopulegone were determined as the major constitutents of the essential oils of Tanacetum species. The findings show that the genus Tanacetum had a considerable variation in essential oil composition.…”
mentioning
confidence: 99%
“…As can be seen from Table 1, the essential oil is composed mainly of monoterpene hydrocarbons (87.9%), followed by oxygenated monoterpenes (4.1%) and oxygenated sesquiterpenes (7.8%). Compared to other Tanacetum species [2][3][4][5][6][7][8][9]11], in this study we found considerable qualitative and quantitative differences in the essential oil composition of Tanacetum sample collected from Ilic. This may be due to genotypic variation and climatic and environmental factors [7].…”
mentioning
confidence: 99%
“…Borneol was the fourth compound of our essential oil (6.0%) and was also a major constituent in several T. polycephalum essential oils [11][12][13], and its derivative, bornyl acetate, was a major structure in the essential oil of T. parthenium [6] and T. Balsamita L. [15]. Lavandulol derivatives comprised 7.3% of our essential oil, and structures with this backbone represent a major portion of T. fruticulosum [7] and T. paradoxum [10] oils. Camphor, which was a major constituent in the essential oil of many Tanacetum species like T. parthenium [6], T. fruticulosum [7], T. khorassanicum [8], T. lingulatum [9], T. paradoxum [10], T. polycephalum [11][12][13][14] and T. Balsamita L. [15], was not detected in our oil.…”
mentioning
confidence: 99%